ANALISIS HUKUM TERHADAP PENERAPAN KEADILAN RESTORATIF (RESTORATIVE JUTICE) DALAM KASUS KEKERASAN DALAM RUMAH TANGGA (STUDI KASUS : POLRES TANAH KARO) - Saina Eunika Y C Br Tarigan; Rayani Saragih; Maslon Hutabalian (Journal Recht (JR), 2025)
This study aims to determine how restorative justice is implemented in resolving domestic violence in Polres Tanah Karo and to determine what factors and obstacles are in the implementation of restorative justice in resolving domestic violence in Polres Tanah Karo. This research method is normative juridical legal research, because it focuses on the implementation of restorative justice as an effort to resolve domestic violence crimes in Polres Tanah Karo. The author uses a normative juridical approach research type, starting by analyzing the regulations governing restorative justice, then analyzing problems in real life in this case conducting interviews in Poles Tanah Karo related to the implementation of restorative justice in resolving domestic violence. The results of the study indicate that the application of restorative justice in resolving domestic violence at the Tanah Karo Police consists of two methods, namely using penal mediation which is carried out by bringing together the two parties to resolve the problem through mediation (deliberation) in a family manner, where the parties involved in mediation are only neutral parties who assist the parties in the negotiation and settlement process through legal channels which will be processed according to applicable law, while the factors and obstacles in the application of restorative justice in resolving domestic violence at the Tanah Karo Police are seen from factors from the victim and perpetrator and factors from the community. Meanwhile, the obstacle in the application of restorative justice is the reluctance of the parties to resolve cases in the police for unknown reasons, for example if there is a summons from the police to conduct mediation, they (the perpetrator/victim) are not present